Anticoagulation and Stroke - Gisela Tinone; Mauricio Hoshino; Leandro Lucato; Luiz Roberto Comerlatti (Arquivos de Neuro-Psiquiatria)
Abstract In 2019, the American Heart Association did not recommend the emergent use of anticoagulation to prevent recurrence or progression of acute ischemic stroke. However, its indication in patients with extracranial artery intraluminal thrombus with artery-to-artery cerebral embolization must be analyzed. In this article, we will also discuss other indications of anticoagulation. This treatment could be indicated in patients with ischemic stroke caused by embolization from cervical artery dissection, catastrophic antiphospholipid antibodies syndrome (APS) and some cases of Covid 19. For secondary prevention, anticoagulation is recommended for Cardioembolic stroke such as nonvalvular atrial fibrillation and other cardiopathies, some patients with cervical artery dissection, stroke associated with cancer, and thrombophilia such as APS. The timing to restart anticoagulation after a large ischemic stroke or after a cerebral hemorrhagic transformation always represent a challenge. Even in patients with high risk of thromboembolism it should be delayed at least two weeks, ideal after four weeks.